Studying satisfaction and spending willingness of guests visiting spas and thermal baths in the Northern Hungarian Region - Szabó , Róbert (Applied Studies in Agribusiness and Commerce, 2013)
In my study I will show the opinion of the guests familiar with seven thermal baths of the Northern-Hungarian Region (such as Eger Thermal Bath, Eger Turkish Bath, Egerszalók Salt Hill Thermal Spa, Demjén Thermal Bath, Bogács Thermal Bath and the Cave-Bath of Miskolc-tapolca) about the medical supply elements, about the price-value rate of supply elements in the thermal bath, and also the spending willingness of the guests in relation to age and earns. From the data I calculated mean, SD and spectrum and examined the crosstab correlations as well, and the Cramer’s V associate coefficient. The results of the correlation tests could be summarised as the following: Guests regardless financial state and age give grade 4 to price/value ratio, but despite their positive judgement spending is not characteristic (most guests spend nothing additional besides admission fee, if so, they do not exceed the 5000 forint amount) even among those who belong to the ’upmarket’ category. Both younger and elderly guests can be characterised with the economical approach, i.e. “Make both ends meet” although seemingly they could extend these “ends”.